Elastase activity on sputum neutrophils correlates with severity of lung disease in cystic fibrosis - Dittrich, A. Susanne; Kühbandner, Iris; Gehrig, Stefanie; Rickert-Zacharias, Verena Martina; Twigg, Matthew; Wege, Sabine; Taggart, Clifford C.; Herth, Felix; Schultz, Carsten; Mall, Marcus A. (The European respiratory journal, 2018)
Neutrophil elastase (NE) is a key risk factor for severity of cystic fibrosis (CF) lung disease. Recent studies identified increased NE activity on the surface of airway neutrophils from CF-like mice and patients with CF. However, the role of surface-bound NE in CF lung disease remains unknown. We determined the relationship between surface-bound NE activity and severity of lung disease in CF. - Surface-bound NE activity was measured on sputum neutrophils from 35 CF patients and eight healthy controls using novel lipidated Förster resonance energy transfer reporters and correlated with free NE activity, neutrophil counts, interleukin-8, myeloperoxidase and antiproteases in sputum supernatant, and with lung function parameters. - Surface-bound NE activity was increased in CF compared to healthy controls (p<0.01) and correlated with free NE activity (p<0.05) and other inflammation markers (p<0.001). Surface-bound and free NE activity correlated with forced expiratory volume in 1 s % predicted (p<0.01 and p<0.05), but only surface-bound NE activity correlated with plethysmographic functional residual capacity % pred (p<0.01) in patients with CF. - We demonstrate that surface-bound NE activity on airway neutrophils correlates with severity of lung disease in patients with CF. Our results suggest that surface-bound NE activity may play an important role in the pathogenesis and serve as novel biomarker in CF lung disease. - Tweetable abstract ERSpublications - click to tweetSurface-bound elastase activity on sputum neutrophils correlates with severity of lung disease in cystic fibrosis http://ow.ly/SRcT30iziHe
Gesehen am 17.03.2020